2018
DOI: 10.1186/s12979-017-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of high sensitivity C-reactive protein and incident Alzheimer disease in patients 60 years and older: The HUNT study, Norway

Abstract: BackgroundWith ageing, long-standing inflammation can be destructive, contributing to development of several disorders, among these Alzheimer’s disease (AD). C-reactive protein (CRP) is a relatively stable peripheral inflammatory marker, but in previous studies the association between highly sensitive CRP (hsCRP) and AD have shown inconsistent results. This study examines the association between AD and hsCRP in blood samples taken up to 15 years prior to the diagnoses of 52 persons with AD amongst a total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Inflammation is increasingly implicated in neurodegenerative diseases such as AD ( Gabin et al., 2018 ; Gong et al., 2016 ; Heneka et al., 2015 ; Kinney et al., 2018 ; Tao et al., 2018 ). Under normal circumstances, inflammation is a protective biological response to infections and injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is increasingly implicated in neurodegenerative diseases such as AD ( Gabin et al., 2018 ; Gong et al., 2016 ; Heneka et al., 2015 ; Kinney et al., 2018 ; Tao et al., 2018 ). Under normal circumstances, inflammation is a protective biological response to infections and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic systemic inflammation can compromise the integrity of the blood–brain barrier, thereby allowing the entry of toxins and pathogens into the brain, and activating glial cells ( Bendorius et al., 2018 ; Kempuraj et al., 2017 ). Blood markers of inflammation have been linked to neurodegenerative conditions including AD ( Gabin et al., 2018 ; Gong et al., 2016 ; Tao et al., 2018 ), cognitive decline ( Noble et al., 2010 ; Watanabe et al., 2016 ), and SVD ( Low et al., 2019 ). However, there has been a lack of research considering longitudinal changes in systemic inflammation in relation to heritable AD risk.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is an acute phase reactant [40] and acts as a mediator of inflammatory and apoptotic processes, including activation of the classical complement pathway [41] and opsonization of atherosclerotic plaques [42]. Recent prospective studies have found that elevated serum CRP levels in midlife may predict increased AD risk, though there is paradoxical shift in which CRP levels decline with advancing age and before clinical AD symptoms appear [43][44][45]. Further, reduced CRP levels in peripheral blood [46][47][48][49] and in CSF [50,51] correlate with increased cognitive dysfunction and further AD progression in an APOE4-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The following dementia-related risk markers indicating cardiometabolic perturbations [ 1 , 2 , 3 , 4 , 5 , 6 ], neurodegeneration [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and vascular dysregulation [ 14 , 15 , 27 ] were specified and included in the current investigation (in no particular order): poorer cognitive executive functioning control [ 30 ]; neuronal glia injury (increased S100B and NSE) [ 19 ]; increased central obesity or waist circumference (WC) [ 32 ]; endothelial dysfuntion (increased von Willebrand factor (VWF)) [ 33 ]; depressed time domain heart rate variability (HRV) ( Supplementary Methodology ) [ 34 ]; increased insulin resistance/HOMA-IR [ 8 ] and inflammation (C-reactive protein/CRP) [ 35 ]; and shorter telomeres [ 21 ].…”
Section: Methodsmentioning
confidence: 99%